1977
DOI: 10.1128/jb.129.1.317-325.1977
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a plasmid involved with enterotoxin B production in Staphylococcus aureus

Abstract: Genetic analysis and molecular characterization of plasmid deoxyribonucleic acid (DNA) was performed in a toxigenic isolate ofStaphylococcus aureus strain DU4916. Elimination, transduction, and transformation experiments provided us with a series of derivatives similar except for the presence or absence of genes mediating resistance to penicillin (penr), methicillin (mecr), and tetracycline (tetr) and enterotoxin type B (SEB) production (entB+). The derivatives were examined for the presence of a plasmid speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
3
4

Year Published

1979
1979
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 24 publications
2
23
3
4
Order By: Relevance
“…However, other studies have shown that SEB synthesis is indeed associated with a particular class of plasmid found in a variety of SEB' isolates. Shalita et al (1977) examined the Dornbusch strain, DU-4916 (KSI 390), and found that the ability to produce SEB was associated with a small plasmid, whose molecular weight was estimated at 0.75 X lo6. This plasmid has since been designated pSN2 and is shown as the peak of fraction 23 in Fig.…”
Section: Genetics Of Sebmentioning
confidence: 62%
“…However, other studies have shown that SEB synthesis is indeed associated with a particular class of plasmid found in a variety of SEB' isolates. Shalita et al (1977) examined the Dornbusch strain, DU-4916 (KSI 390), and found that the ability to produce SEB was associated with a small plasmid, whose molecular weight was estimated at 0.75 X lo6. This plasmid has since been designated pSN2 and is shown as the peak of fraction 23 in Fig.…”
Section: Genetics Of Sebmentioning
confidence: 62%
“…Resistance of S. aureus isolates to various antimicrobial agents may be located either on chromosomes, plasmids or transposons. For example, methicillin resistance gene (mec4916) has a chromosomal locus, and is probably maintained on a mobile element (34,35), while tetracycline resistance observed in S. aureus strain DU4916 was reported to be encoded by a 4.0 kb plasmid (36). Noble and Rahman (37) reported tetracycline resistance in S. aureus to be encoded by a 4.3 kb plasmid, while in some strains resistance was found to be encoded by a chromosomal gene.…”
Section: Discussionmentioning
confidence: 99%
“…Enterotoxin gene locations (Table 5) are numerous (Argudin et al, 2010). They can be carried by plasmids (seb, sed, sej, ser, ses, set) (Shalita et al, 1977;Bayles & Iandolo, 1989;Zhang et al, 1998;Omoe et al, 2003;Ono et al, 2008), phage (temperate for sea, defective for see) (Betley & Mekalanos, 1985;Couch et al, 1988;Coleman et al, 1989) or by genomic islands (seb, sec, seg, seh, sei, sek, sel, sem, sen, seo, sep and seq). Gene encoding for sec can be located on a plasmid or a pathogenicity island depending on the origin of the isolate (Fitzgerald et al, 2001).…”
Section: Genetic Determinants and Regulation Of Expressionmentioning
confidence: 99%
“…The location of se genes on mobile genetic elements can result in horizontal gene transfer between the strains of S. aureus. For example, the seb gene is located on the chromosome in some clinical isolates (Shafer & Iandolo, 1978), whereas it has a plasmidic location in other strains of S. aureus (Shalita et al, 1977). A main regulatory system controlling the expression of virulence factors in S. aureus is the agr system (accessory gene regulator; Kornblum et al, 1990).…”
Section: Genetic Determinants and Regulation Of Expressionmentioning
confidence: 99%